Bridging Transformation: The Power of Human Capital Maturity in Strengthening Corporate Performance at PTPN - Achmad Fadil; Syamsul Ma’arif; Ari Ekananta (JOURNAL OF MANAGEMENT, ACCOUNTING, GENERAL FINANCE AND INTERNATIONAL ECONOMIC ISSUES, 2025)
This study explores the role of Human Capital Maturity Level (HCML) in shaping corporate performance and driving organizational transformation at PTPN, a state-owned plantation company undergoing structural changes. The research examines how different HCML dimensions such as Strategic, Primary, and Foundation influence financial performance and, in turn, impact transformation success. Using Structural Equation Modeling-Partial Least Squares (SEM-PLS), the study identifies key relationships between HCML and corporate outcomes, while Analytical Hierarchy Process (AHP) is applied to determine the most effective transformation strategies based on expert assessments. Findings indicate that HCML Strategic significantly enhances corporate profit (loading = 0.695, p < 0.001), while HCML Foundation strengthens corporate health (loading = 0.552, p < 0.001). The AHP results highlight that Developing HR Capabilities (0.35) is the top priority, followed by Change Management Implementation (0.20) and Digital Transformation (0.15). These insights suggest that structured HRM strategies, competency development, and digital adaptation play a crucial role in ensuring sustainable business transformation. The study offers practical recommendations for HR policymakers and corporate leaders to enhance workforce readiness, optimize change management, and leverage digitalization to maintain competitive advantage.